If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -2 * -1.04 = 0 Multiply -2 * -1.04 6 + 2.08 = 0 Combine like terms: 6 + 2.08 = 8.08 8.08 = 0 Solving 8.08 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -2(2s-3)-6=-3(7s+6)-4 | | 3.92=(4x^2)/(0.5-x) | | 7x-51=96 | | g+5.6=10 | | 2/9x7/11 | | k^2-14k+86=0 | | (1/4)(x-3)=-15 | | (6x-1)2=17 | | 4(x+1)^1/2-5(x+1)^3/2+(x+1)^5/2=0 | | (5/8)x=-25 | | 9=2x-10 | | -1y=2x | | W-1.94=5.2 | | 2(x+4)=3(x+9) | | 6+2.3y=3.6 | | k^2-6k+64=0 | | 3x-1=6561 | | 6h-4=5h-4 | | -3+3y=9 | | 4x-20=2y | | 0.20x+0.15(70)=25 | | -5z^2-4z+5=0 | | 2/7x5922 | | 65.13=13x | | 9(2x+1)=5x-8x | | .75(6+x)=12 | | -3+.2*7.5= | | 23x-59x=2 | | X(9x+18)=4x^2-4x+15 | | 2x-10y=15 | | 2w^2+8w-270=0 | | -11+9=-2(x+4) |